Pemberdayaan Komunitas Save Street Child Sebagai Solusi Pendidikan Anak Marjinal Di Kabupaten Sidoarjo Jawa Timur - Ichwayudi, Budi; Ilmiyah, Dakhirotul; Rochma, Ega Dini Nur (Proceedings of Annual Conference on Community Engagement, 2022)
Sidoarjo City is one of the cities in East Java which has a high APBD but in the reality of community economic growth there are still various disparities between the rich man and the poor man, so that various problems arise in tackling the educational empowerment of marginalized children. This study tries to provide solutions to these problems through community empowerment based on the Save Street Child community, one of the basis of which is to provide broad access for marginalized children in the city of Sidoarjo in order to survive in terms of education and skills. The approach used in this study is the PAR (Participatory Action Research) method in order to identify various existing problems and provide solutions to problems. This study concludes that the Save Street Child community tries to provide breakthrough solutions in terms of educating marginalized children so as not to become beggars and buskers, namely by providing various training and work skills as well as providing additional lessons or private lessons with a time that can be adjusted to their busy schedule action.